2020
DOI: 10.2486/indhealth.2018-0111
|View full text |Cite
|
Sign up to set email alerts
|

Chronic pesticide mixture exposure including paraquat and respiratory outcomes among Colombian farmers

Abstract: This study explored the potential association between chronic exposure to pesticide mixtures including paraquat and respiratory outcomes among Colombian farmers. Sociodemographic and occupational data, respiratory symptoms and spirometric data were collected. Paraquat in spot urine samples were quantified with solid-phase extraction high-performance liquid chromatography. Multiple Poisson regressions with robust variance were used to determine factors associated with respiratory outcomes. Profiles of pesticide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In addition, a cross-sectional study by Arroyo et al (2018) [24] found that exposure to pesticides in the last 12 months was associated with asthma (OR = 1.55, 95%CI: 1.10-2.18). With regard to any association between herbicides and asthma, a study by Diaz-Criollo et al (2020) [16] showed that paraquat was associated with self-reported asthma with a prevalence rate of 1.06 (1.00-1.13). A study of Cha et al (2012) [25] also found the association between paraquat application and adverse respiratory health effects among farmers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a cross-sectional study by Arroyo et al (2018) [24] found that exposure to pesticides in the last 12 months was associated with asthma (OR = 1.55, 95%CI: 1.10-2.18). With regard to any association between herbicides and asthma, a study by Diaz-Criollo et al (2020) [16] showed that paraquat was associated with self-reported asthma with a prevalence rate of 1.06 (1.00-1.13). A study of Cha et al (2012) [25] also found the association between paraquat application and adverse respiratory health effects among farmers.…”
Section: Discussionmentioning
confidence: 99%
“…The inhalation of insecticides can cause serious damage to the nose, the throat, and lung tissues, causing inflammation of the airways and frequently leading to chronic respiratory disease [ 15 ]. According to previous studies, occupational exposure to insecticides is associated with an increased risk of the respiratory symptoms common in asthma and chronic bronchitis [ 16 ]. However, some studies have not found any association between insecticide exposure and asthma [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the active substances there are also products that are already banned or soon to be banned in the European Union. An example is paraquat (Gramoxon©), mentioned by pesticide users in existing studies [38] and banned in the EU since 2007 [39].…”
Section: Pesticides Usedmentioning
confidence: 99%
“…Our cohort had a similar prevalence of rhinitis (9%) to a recent study in Colombia, which had a rhinitis prevalence of 10% and observed an increased risk for rhinitis in adults exposed to mixtures of paraquat, profenofos and glyphosate. 38 Similarly, a study of grape farmers in Greece had a higher prevalence of allergic rhinitis (37%) and found positive associations between use of some pesticides and allergic rhinitis. Consistent with our findings, this study did not find evidence of an association between OPs and rhinitis.…”
Section: Discussionmentioning
confidence: 96%